Pengaruh Iklim Organisasi Dan Beban Kerja Terhadap Komitmen Guru Di SMK Negeri 1 Surakarta - Elisa Estarini; Cicilia Dyah Sulistyaningrum Indrawati; Hery Sawiji (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine; 1) influence of organizational climate on teacher commitment, 2) influence of workload on teacher commitment, 3) influence of organizational climate and workload simultaneously on teacher commitment. This research was conducted at SMK Negeri 1 Surakarta. This study uses a quantitative approach with correlational methods. The population in this study were all subject teachers, totaling 62 people, with the research sample using a saturated sampling technique. The data was collected by Likert scale questionnaire.